The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jpsychires.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive triple chronotherapy (combined total sleep deprivation, sleep phase advance, and bright light therapy) rapidly improves mood and suicidality in suicidal depressed inpatients: An open label pilot study

Abstract: Previous studies have demonstrated that combined total sleep deprivation (Wake therapy), sleep phase advance, and bright light therapy (Triple Chronotherapy) produce a rapid and sustained antidepressant effect in acutely depressed individuals. To date no studies have explored the impact of the intervention on unipolar depressed individuals with acute concurrent suicidality. Participants were suicidal inpatients (N=10, Mean age=44±16.4SD, 6F) with unipolar depression. In addition to standard of care, they recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 36 publications
0
32
0
3
Order By: Relevance
“…Sleep deprivation in conjunction with lithium and light therapy has also been demonstrated to rapidly reduce suicidal thoughts in BD patients 31 but, to our knowledge, no systematic studies of the ability of sleep deprivation alone to reduce suicidal thoughts has been conducted 32 . Even with these seemingly contradictory findings, the sleep deprivation literature in both healthy volunteers and depressed patients underscores the importance of sleep in suicide risk and the potential of sleep-focused interventions for the treatment of suicidal patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep deprivation in conjunction with lithium and light therapy has also been demonstrated to rapidly reduce suicidal thoughts in BD patients 31 but, to our knowledge, no systematic studies of the ability of sleep deprivation alone to reduce suicidal thoughts has been conducted 32 . Even with these seemingly contradictory findings, the sleep deprivation literature in both healthy volunteers and depressed patients underscores the importance of sleep in suicide risk and the potential of sleep-focused interventions for the treatment of suicidal patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that wake therapy in combination with other chronotherapeutic interventions can produce a sustained antidepressant effect, and clinical benefits are seen even in treatment-resistant patients (Echizenya et al 2013;Martiny et al 2012Martiny et al , 2015Michalak et al 2007;Sahlem et al 2014;Wu et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…33 Tripartite interventions (total or partial SD þ light therapy þ SPA) implemented in small open trials also yielded remission rates of 60% to 75%. 31,34,35 The most common side effect of SD is daytime sleepiness. Recurrence of panic attacks has been noted during SD, 24 but with no adverse impact on treatment of comorbid depression.…”
Section: What Is Sleep Deprivation? How Effective Is Sleep Deprivatiomentioning
confidence: 99%